2012
DOI: 10.1017/s0031182012000911
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new species of digenean Notocotylus malhamensis n. sp. (Digenea: Notocotylidae) from the bank vole (Myodes glareolus) and the field vole (Microtus agrestis)

Abstract: Notocotylus malhamensis n. sp. is described from the caecum of the bank vole (Myodes glareolus) and the field vole (Microtus agrestis) from Malham Tarn Nature Reserve in North Yorkshire, UK. In total, 581 specimens were collected from rodents trapped at a wetland site (Tarn Fen) between July 2010 and October 2011 with a prevalence of 66·7% and mean intensity of 94·6 in the bank vole and 50% prevalence and a mean intensity of 4·3 in the field vole. This species appears to be most closely related to other previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…No information is available on the pathogenicity of this parasite. Apart from the epidemiological and molecular findings on Notocotylidae members that have already been demonstrated by other researchers (Smith 1954;Beckett and Gallicchio 1967;Beverley-Burton and Sweeny 1972;Wittrock 1976;Shuteev 1977;Radlett 1980;MacKinnon 1982;Schuster 1986;Namue and Wongsawad 1997;Seegers et al 1997;Kinsella and Tkach 2005;Flores and Brugni 2003;Kirillova and Kirillov 2009;Birmani et al 2011;Chaisiri et al 2011;Yousif et al 2011;Boyce et al 2012;Detwiler et al 2012;Iwaki et al 2012;Skála et al 2014), there is a paucity of information on the morphology of Q. quinqueserialis using light and electron microscopy (Rausch 1952;Kinsella 1971;Beverley-Burton et al 1976;Wittrock 1986). For the first time, the present SEM study provides more details of this trematode, removed from the intestine of an infected muskrat.…”
Section: Introductionmentioning
confidence: 78%
“…No information is available on the pathogenicity of this parasite. Apart from the epidemiological and molecular findings on Notocotylidae members that have already been demonstrated by other researchers (Smith 1954;Beckett and Gallicchio 1967;Beverley-Burton and Sweeny 1972;Wittrock 1976;Shuteev 1977;Radlett 1980;MacKinnon 1982;Schuster 1986;Namue and Wongsawad 1997;Seegers et al 1997;Kinsella and Tkach 2005;Flores and Brugni 2003;Kirillova and Kirillov 2009;Birmani et al 2011;Chaisiri et al 2011;Yousif et al 2011;Boyce et al 2012;Detwiler et al 2012;Iwaki et al 2012;Skála et al 2014), there is a paucity of information on the morphology of Q. quinqueserialis using light and electron microscopy (Rausch 1952;Kinsella 1971;Beverley-Burton et al 1976;Wittrock 1986). For the first time, the present SEM study provides more details of this trematode, removed from the intestine of an infected muskrat.…”
Section: Introductionmentioning
confidence: 78%
“…1). Species of the genus Notocotylus are defined as a cosmopolitan group parasitising waterfowl and small aquatic mammals (Boyce et al, 2012), whereas species of Catatropis are all parasites of birds and C. indicus specifically of ducks (Koch, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Brachylaima recurva ), typically found infecting the pancreatic ducts and the small intestine, respectively, of their host (Elton et al , 1931; Lewis, 1968; Lewis & Twigg, 1972; Behnke et al , 1999; Abu-Madi et al , 2000). The parasites of A. sylvaticus and other small mammals have been studied extensively in populations located in a periaquatic environment at the Malham Tarn Nature Reserve, North Yorkshire, UK (Allan et al , 1999; Hughes et al , 2006, 2008; Rogan et al , 2007; Hide et al , 2009; Thomasson et al , 2011) including the discovery of a new digenean species (Boyce et al , 2012). Specifically, Rogan et al (2007) reported the occurrence of the intestinal digenean Plagiorchis muris in the wood mouse A. sylvaticus over a 13-year period with an overall prevalence of 16.9%.…”
Section: Introductionmentioning
confidence: 99%